Life history traits for Ophryotrocha craigsmithi (Wiklund, Glover & Dahlgren, 2009), a candidate species in integrated multitrophic aquaculture - Svensson, Signe Gunborg Bentzrød; Strohmeier, Tore; Rastrick, Helen; Garcia, Antonio Aguera; Lock, Erik-Jan; Sveier, Harald; Jansen, Henrice M. (Frontiers in Marine Science, 2023)
Ophryotrocha craigsmithi Wiklund, Glover & Dahlgren 2009, has repeatedly been observed in high densities at salmonoid fish farms in Norway and has been shown to feed on the organic waste released during fish production. Although Ophryotrocha is a well-studied genus for species occupying shallow and warmer waters, little is known about the life history traits of Ophryotrocha species found at greater depths in temperate waters. This species has been pointed out as a candidate for the benthic part of integrated multitrophic aquaculture (IMTA). O. craigsmithi is an unusually large Ophryotrocha species ( 17 mm), often found at depths of 60-200 m. In this laboratory study, we aimed to describe key life history traits of this species that are of importance for evaluating the population dynamics, such as growth, reproductive pattern and offset of reproduction. The main findings showed that they exhibit common life history traits described for the genus with early sexual maturation and rapid growth, going from 5 mm in length to 16 mm in 8 weeks. There are strong indications for these being gonochoric semi-continuous spawners. Naturally spawned eggs diameter ranged from 120 to 200 µm, with the majority of eggs occupying the range from 120 to 150 µm. The larvae developed into a free-swimming stage after approximately one week. Insight into these traits is of key importance in evaluating the bio-mitigation potential of (benthic) species within IMTA systems. To this end, we present a framework for assessing the suitability of deposit-feeding polychaetes as candidate species in IMTA, considering environmental adaptiveness, production potential as well as mitigation capacity. Based on this, O. craigsmithi shows high suitability as an extractive species in benthic IMTA.